Relay Selection in Adaptive Buffer-Aided Space-Time Coding with TAS for Cooperative Wireless Networks - Ahvanth, B.; Ramassamy, E. (Asian Journal of Engineering and Applied Technology, 2017)
In this work, we propose an adaptive buffer-aided space-time coding scheme for cooperative wireless networks. A maximum likelihood receiver and adjustable code vectors are considered subject to a power constraint with an amplify-and forward cooperation strategy. Each relay is equipped with a buffer and is capable of storing the received symbols before forwarding them to the destination. We also present an adaptive relay selection and a new hybrid relay selection protocol, in which the instantaneous signal to noise ratio in each link is calculated and compared at the destination. The transmit antenna selection (TAS) is adopted at the destination where a single transmit antenna at the transmitter and relay that maximizes the instantaneous received signal-to-noise ratio is selected for further transmissions to improve the performance of co-operative network. A stochastic gradient algorithm is then developed to compute the parameters of the adjustable code vector with reduced computational complexity. Simulation results show that the proposed buffer-aided schemes with TAS obtain performance gains over existing schemes.